A Critical Tiriti Analysis of the recruitment and performance review processes of public sector chief executives in Aotearoa - Moahuia Goza; Heather Came; Isla Emery‐Whittington (Elsevier, 2022)
Abstract Objective: Breaches of Te Tiriti o Waitangi (Te Tiriti) and evidence of institutional racism have been consistently documented within the public sector for decades. Chief executives across the sector have a critical responsibility to lead the implementation of the Crown's Te Tiriti o Waitangi responsibilities. This paper examines the recruitment and performance review processes of public sector chief executives from 2000 to 2020 to ascertain Te Tiriti compliance. Methods: Recruitment and performance review templates were obtained via official information requests to Te Kawa Mataaho Public Service Commission. The data were analysed using a five‐stage Critical Tiriti Analysis to determine compliance based on indicators developed around the five elements of Te Tiriti. Results: Our study found no explicit evidence of engagement with te Tiriti in any aspect of the recruitment and or performance review processes in the documents released. Conclusions: This appears to be another contemporary breach of Te Tiriti that urgently needs to be addressed prior to the new round of appointments in the health sector. Implications for public health: With significant senior appointments about to be made within the health sector, this paper is a timely contribution to the wider debate about the implications of the WAI 2575 Waitangi Tribunal report on the health sector.